Genomic analysis reveals high virulence and antibiotic resistance amongst phage susceptible Acinetobacter baumannii - Leungtongkam, Udomluk (Sci Rep, 2020)
In this study, we examined the association between antimicrobial resistance, CRISPR/Cas systems and virulence with phage susceptibility in Acinetobacter baumannii and investigated draft genomes of phage susceptible multidrug resistant A. baumannii strains from Thailand. We investigated 230 A. baumannii strains using 17 lytic A. baumannii phages and the phage susceptibility was 46.5% (107/230). Phage susceptibility was also associated with resistance to numerous antibiotics (p-value < 0.05). We also found association between biofilm formation and the presence of ompA gene among phage susceptible A. baumannii strains (p-value < 0.05). A. baumannii isolates carrying cas5 or combinations of two or three other cas genes, showed a significant increase in phage resistance. Whole-genome sequences of seven phage susceptible A. baumannii isolates revealed that six groups of antibiotic resistance genes were carried by all seven phage susceptible A. baumannii. All strains carried biofilm associated genes and two strains harbored complete prophages, acquired copper tolerance genes, and CRISPR-associated (cas) genes. In conclusion, our data exhibits an association between virulence determinants and biofilm formation among phage susceptible A. baumannii strains. These data help to understand the bacterial co-evolution with phages.